Evaluate the Effect of Chemotherapy on Tear Film in Breast Cancer - Musfira Asif; Ammara Affi; Maimouna Allahbakhsh; Tahreem Fatima; Anita Zulfiqar; Umm e Sulaim (Medical Journal of South Punjab, 2024)
Objective: The aim of study is to evaluate the effect of different sessions of chemotherapy in breast cancer females on tear film. Methods: An observational longitudinal study was conducted at the oncology department of Madinah Teaching Hospital Faisalabad from September 2023 to December 2023. A purposive non- probability sampling technique was used to select the data. 30 Females with 25-45years of age, diagnosed with breast cancer having chemotherapy as treatment plan were included. Exclusion criteria was contact lens users, seasonal allergies, lactating woman, menopausal woman and past history of dry eye. After taking verbal and written consent and complete history, Schirmer test and TBUT was performed at baseline and after 2, 4 and 6 sessions of chemotherapy. Then compared their results. Result: Data was analyzed with Repeated Measure ANOVA test by using IBM SPSS software version20. The mean difference of tear film stability and production at baseline in breast cancer females was 14.3333±2.998 and 14.300±3.425 respectively. After 3 cycles of chemotherapy cycles the mean difference of TBUT and Schirmer was reduced with P=0.00. Conclusion: The incidence of aqueous-deficient dry eye was significantly higher in patients who had undergone more than two sessions of chemotherapy. As number of sessions increases, lower the value of Schirmer I and TBUT were recorded. KEYWORDS: Dry Eye, Schirmer, Chemotherapy, Breast Cancer, aqueous-deficient dry eye.